ANALISIS BIAYA, PENDAPATAN DAN EFISIENSI USAHATANI SAYURAN DATARAN TINGGI DENGAN BERBAGAI POLA TANAM DI DESA SUMBER URIP KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Badrudin, Redy; Sumantri, Bambang; Paris, Edi (Jurnal AGRISEP, 2005)
This research was aimed at estimating production cost, income and economic eficiency of various patterns of high land vegetables farming. This research was carried out on August until September 2004 in Sumber Urip village subdistrict Selupu district of Rejang Lebong. Stratified Random Sampling with equal alocation of 63 respondents was apllied. These respondents then be stratified into 7 strata based on their cultivation patterns. This research resulted the highest the average total cost of monoculture patterns is farmed with cabbage pattern while for polyculture pattern is cabbage inter cultivated with onion leaves The highest income on the monoculture crop pattern, is cauliflower cultivation with onion leaves is the highest for policultuere the highest eficiency for monoculture pattern of cultivate was on cauliflower and for polyculture is onion leafes farming .